2019
DOI: 10.1016/j.wneu.2018.10.035
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Blood Coagulation After Aneurysmal Subarachnoid Hemorrhage: A Prospective Observational Trial of Rotational Thromboelastometry

Abstract: Objectives: Aneurysmal subarachnoid haemorrhage (aSAH) is reported to actuate blood coagulation. Rotational thromboelastometry (ROTEM) is a dynamic haemostatic test that can differentiate various coagulation abnormalities, for example, increased coagulation activity can be detected as a wider amplitude of tracing (maximal clot firmness [MCF]). Previously, ROTEM has not been used to evaluate coagulation changes after aSAH. The aim of this prospective, observational study was to evaluate the ongoing coagulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(36 citation statements)
references
References 43 publications
(54 reference statements)
3
33
0
Order By: Relevance
“…The role of TEG in general in neurosurgery-with or without PM-remains unproven, but promising reports are proliferating. 11,12,17,18,22,27,32 Conclusions TEG-PM is ineffective in predicting complications in endovascular neurosurgery patients. Its use for this indication is questionable, although further study is necessary in this regard.…”
Section: Fig 3 Bar Charts Demonstrating Dose-response Relationship Between Pru and Both Hemorrhage (A) And Thrombosis (B) Ratesmentioning
confidence: 94%
“…The role of TEG in general in neurosurgery-with or without PM-remains unproven, but promising reports are proliferating. 11,12,17,18,22,27,32 Conclusions TEG-PM is ineffective in predicting complications in endovascular neurosurgery patients. Its use for this indication is questionable, although further study is necessary in this regard.…”
Section: Fig 3 Bar Charts Demonstrating Dose-response Relationship Between Pru and Both Hemorrhage (A) And Thrombosis (B) Ratesmentioning
confidence: 94%
“…[53][54][55]57,66,67 However, while four studies found hypercoagulation on admission, 53,54,57,66 two studies did not reveal hypercoagulation until 72 hours after ictus. 55,67 Between studies, clot initiation, amplifica-tion, and strength were changed to different degrees. While the low tissue factor ROTEM assay revealed changes toward hypercoagulation in all phases of coagulation on admission, 53 the commercially available ROTEM assay revealed only increased clot strength 54 ; however, this was revealed in both ExTEM and FibTEM maximum clot firmness.…”
Section: Secondary Hemostasismentioning
confidence: 99%
“…Overall, mean platelet count on admission was within reference range or equivalent to the control group in all studies measuring this. 30,31,36,[49][50][51][52][53][54][55][56] In one study, the platelet count was higher in aSAH patients than in the control group, but a reference range was not provided. 57 When measured over days following aSAH, platelet count tended to decrease with a minimum between days 4 and 14.…”
Section: Primary Hemostasismentioning
confidence: 99%
See 2 more Smart Citations